1990
DOI: 10.1590/s0006-87051990000200018
|View full text |Cite
|
Sign up to set email alerts
|

Controle das plantas daninhas na cultura de alface transplantada com o herbicida oxadiazom

Abstract: Efetuou-se um experimento com o herbicida oxadiazom, objetivando estudar o efeito do seu uso no controle das plantas daninhas e na, produção da cultura da alface transplantada. Os tratamentos, em número de sete, consistiram em três doses de oxadiazom formulado em grânulos, 1,0,1,5 e 2,0kg/ha, aplicadas após o transplante da alface, dois fratamentos de 1,0kg/ha do herbicida formulado em concentrado emulsionável, um pulverizado antes e, outro, após o transplante, em área total, e duas testemunhas, uma capinada e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
1
0
2
Order By: Relevance
“…SANCHEZ (1999) and GARCIA et al (1982) affirm that the slowness of dry and fresh mass accumulation in the early cycle constitutes the main factor of sensibility to competition, especially since in this period the transplanted crop is still establishing. Under normal conditions of used spacing, the studies showed that the prior periods of interference are situated between the 20 and 25 DAT (APPEZZATO et al, 1983;PAULO et al, 1990;SANCHEZ, 1999;MELHORANÇA FILHO et al, 2008), agreeing with the results obtained in this study. …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…SANCHEZ (1999) and GARCIA et al (1982) affirm that the slowness of dry and fresh mass accumulation in the early cycle constitutes the main factor of sensibility to competition, especially since in this period the transplanted crop is still establishing. Under normal conditions of used spacing, the studies showed that the prior periods of interference are situated between the 20 and 25 DAT (APPEZZATO et al, 1983;PAULO et al, 1990;SANCHEZ, 1999;MELHORANÇA FILHO et al, 2008), agreeing with the results obtained in this study. …”
Section: Resultssupporting
confidence: 90%
“…From the weed plants present in the experimental area stood out in quantity the Digitaria horizontalis L. Wild, Spermacoce latifolia Aubl, Cyperus rotundus and the Euphorbia heterophyla L. These species constituted 83.8% of the spontaneous weed plants (Table 1), being found regularly in the vegetables cultivations (PEREIRA, 1987;PAULO et al, 1990;PEREIRA, 2000;HORTA et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Entretanto Paulo et al (1990), ressaltam que a dose e o cultivar influenciam na tolerância das plantas de alface aos herbicidas, e consequentemente nos efeitos fitotóxicos ocasionados por essas moléculas. Dessa forma, o nível de severidade dos herbicidas sobre as plantas de alface em virtude da deriva, será em função da época de aplicação e/ou estágio fenológico das plantas de alface.…”
Section: Introductionunclassified
“…Áreas cultivadas em geral, apresentam condições favoráveis para o surgimento de espécies de plantas espontâneas denominadas "plantas daninhas". Essas competem com as plantas cultivadas pelos mesmos fatores de sobrevivência, tais como luz, nutrientes, espaço e água, acarretando diminuição da produtividade (Paulo et al, 1990) e perdas na qualidade dos grãos. Dependendo de diversos fatores, tais como nutrientes, luminosidade, espaço e umidade do solo, algumas espécies daninhas podem se expressar com maior ou menor vigor e intensidade.…”
Section: Introductionunclassified